ANALISIS PROFITABILITAS PERBANKAN SEBELUM DAN SESUDAH MENERAPKAN FINTECH - Salsabila, Faiza Bela; Jiwa Juwita, Himmiyatul Amannah (Jurnal Management Risiko dan Keuangan, 2022)
The rapid development of information technology and the internet, which are more becoming community-oriented, has an impact on the emergence of financial technology or what is often called fintech. Collaboration between Fintech and Banking institutions will bring benefits to each party. This research is intended to measure the effect of the collaboration between banking and fintech. This research is a quantitative study with comparative analysis that aims to measure the differences in profitability levels as measured by the ratio of Return On Assets (ROA), Return on Equity (ROE), Net Interest Margin (NIM), and Operating Expenses on Operating Income (BOPO) between before and after implementing fintech in banking with a sample of government banks listed on the IDX for the 2015-2020 period that have collaborated with fintech startups. Data analysis used Paired T Test and Wilcoxon Ranked Signed Test. The results showed that there were significant differences in ROA, ROE, and NIM at 3 out of 7 Banks after implementing fintech, but the difference was a decrease. The implication of this research is that there is still a need for improvement in banking and there is still a need for adjustments from banks to remain profitable while following technological advances.